Vitamin D deficiency: Plethora of Etiological Factors Prevalent in Pakistan - Ayesha Saba Naz (Journal of Bahria University Medical and Dental College)
Vitamin D, known as cholecalciferol, is a lipid soluble vitamin. Vitamin D (VD) has tremendous array of functions in the body; especially it plays a vital role in the health of the skeletal tissues. It strictly cannot be regarded as a vitamin since a substantial amount of the vitamin can be produced by the effect of sunlight on the skin. The insufficiency or deficiency of VD is growing worldwide and has assumed a pandemic situation. There are various factors contributory towards the development of vitamin D deficiency. Even in Pakistan, where sun drenched climate prevails, this alarming situation is growing and getting worse day by day. There are copious factors; like pervasiveness of sun protection practices, improper exposure to sun, lesser avenues of outdoor recreational activities, gender hindrances, biological factors etc. Lack of awareness and negligence are making this situation go even grim. In this review, the contributory factors, especially those more widespread in Pakistan are kept in view and are amalgamated in this article. Recent literature from our part of the world and after that from Asia had been preferred so that our population could connect, relate and benefit from it well.